2018
DOI: 10.1002/hpja.43
|View full text |Cite
|
Sign up to set email alerts
|

The “ripple effect”: Health and community perceptions of the Indigenous Marathon Program on Thursday Island in the Torres Strait, Australia

Abstract: Positive "ripple" effects of the IMP on running and broader health were described to have occurred through local role modelling of healthy lifestyles by IMP runners that reduced levels of "shame" and embarrassment, a common barrier to physical activity among Indigenous Australians. A high initial level of community readiness for behaviour change was also reported. SO WHAT?: Strategies to overcome this "shame" factor and community readiness measurement should be incorporated into the design of future Indigenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(57 citation statements)
references
References 20 publications
2
55
0
Order By: Relevance
“…No studies scored “Yes” for all 14 categories. The highest scoring study scored “Yes” in 11 of the 14 categories [ 35 ], followed by a study scoring 10/14 [ 36 ] and five further studies scoring 7/14 [ 18 , 32 , 37 , 38 , 39 ]. All studies included scores of “Partial” and “Unclear” in several categories.…”
Section: Resultsmentioning
confidence: 99%
“…No studies scored “Yes” for all 14 categories. The highest scoring study scored “Yes” in 11 of the 14 categories [ 35 ], followed by a study scoring 10/14 [ 36 ] and five further studies scoring 7/14 [ 18 , 32 , 37 , 38 , 39 ]. All studies included scores of “Partial” and “Unclear” in several categories.…”
Section: Resultsmentioning
confidence: 99%
“…All 11 included studies were published between 2010 (Abbott et al, 2010;Foley, 2010) and 2019 (Brown et al, 2019;Seear et al, 2019). Three studies were conducted in the Australian State of Queensland (Brown et al, 2019;Foley, 2010;Sushames et al, 2017), two each in Western Australia (Nilson et al, 2015;Seear et al, 2019), and South Australia (Canuto et al, 2013;Tsourtos et al, 2014) and one each in New South Wales (Abbott et al, 2010), and the Northern Territory (Thompson et al, 2013) and a statutory authority of Australia called the Torres Strait Islands (Macniven et al, 2018). Additionally, one study was conducted across four Australian States-Victoria, Western Australia, South Australia, and New South Wales (Chapple et al, 2016).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Additionally, one study was conducted across four Australian States-Victoria, Western Australia, South Australia, and New South Wales (Chapple et al, 2016). Six studies (Brown et al, 2019;Chapple et al, 2016;Macniven et al, 2018;Nilson et al, 2015;Seear et al, 2019;Thompson et al, 2013) reported that they were conducted in remote Indigenous communities. The data collection methods for the 11 included primary studies were via interviews (semi-structured and unstructured) individually or focus groups (often referred to in the Indigenous communities as yarning groups).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations